Nitric oxide-sensing mechanisms in Escherichia coli. (20th January 2006) - Spiro, S.
Abstract : Exposure of Escherichia coli to nitric oxide (NO) or nitrosating agents causes significant changes in patterns of gene expression. Three recent studies have used microarrays to analyse the response of the E. coli transcriptome to NO and nitrosative stress. Drawing on the array data, I review our current understanding of the E. coli regulatory systems that are involved.